The role of students in building a nation based on Pancasila - Khairi Wilda Prihati; Salam Salam; Rahma Dani (Indonesian Institute for Counseling, Education and Theraphy, 2021)
It is not easy to maintain what has been obtained by youth in the past, this is influenced by several factors including environmental factors. The dynamics of the development of the environment is very felt by the currents of globalization, modernization, this feels very well in the environment both nationally and internationally. Everything that happens greatly influences the thinking patterns, attitudes and actions of the younger generation in dealing with the problems facing the nation. On the other hand, the younger generation was traumatized by political attitudes during the New Order government which gave birth to a generation of apathetic reforms who did not care about the noble values that existed in Pancasila. Meanwhile, the demands of globalization have changed the perception of what is happening in the country. The threat that occurs is no longer as it used to be tangible or physical in nature, but has covered all concrete and abstract aspects of life. Therefore, the implementation of Pancasila values in life is very much needed to be a reference for the Indonesian people to answer various problems faced when this and the future, both problems that come from within and from outside.